Aktivitas Antibakteri Ekstrak dan Fraksi Kulit Buah Jambu Biji (Psidium guajava L.) serta Analisis Bioautografi terhadap Pertumbuhan Staphylococcus aureus - Rista Dias Yunitasari; Ana Indrayati; Reslely Harjanti (Fakultas Farmasi Universitas Setia Budi, 2025)
Guava (Psidium guajava L.) is a plant from the Myrtaceae family that is widely found in Indonesia. Guava skin contains flavonoids, alkaloids, saponins, tannins and terpenoids that have the potential to overcome various infections. This study aims to determine the antibacterial activity of guava skin extracts and fractions and to determine the group of compounds from the most active extract or fraction against the growth of Staphylococcus aureus using the bioautography method. Guava skin was extracted by the maceration method using 70% ethanol solvent, then fractionated using n-hexane, ethyl acetate, and water solvents to optimize the separation of substances. Antibacterial activity testing of guava fruit peel extract and fractions was done with concentrations of 8, 10, and 12%, positive control ciprofloxacin, and negative control DMSO 3%. Diffusion results were obtained from measuring the diameter of the inhibition zone around the disc paper. The results of the largest diameter were continued to determine the compound group of the most active extract or fraction through bioautography tests. The results showed that a concentration of 12% in the water fraction had the largest diameter of 16.55 mm which was included in the strong category. The water fraction that showed the most active antibacterial activity was then subjected to the bioautography method. The results obtained showed the presence of flavonoid compounds at Rf 0.34 with a diameter of 1.1 mm in the water fraction and 1.2 mm in the quercetin standard.